2019
DOI: 10.1002/pmrj.12120
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Level of Concussion Knowledge in High School Sports in New Jersey

Abstract: Background Coaches, athletic trainers (ATCs), and parents/guardians (parents) are important contributors to the proper identification and management of concussions in student‐athletes. However, there are limited studies on the identification of concussion knowledge gaps that will help inform educational efforts and improve concussion outcomes in these groups. Objective To identify gaps and factors influencing concussion knowledge for high school athletics. Design Survey. Setting Public, private, and recreation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…McLeod et al ( 10 ) found that, while coaches could identify overt symptoms of concussion, they could not identify more subtle signs and symptoms such as sleep disturbances and vision problems. Lin et al ( 18 ) also found similar knowledge gaps about concussions. Both studies advocate for more specific education on concussion.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…McLeod et al ( 10 ) found that, while coaches could identify overt symptoms of concussion, they could not identify more subtle signs and symptoms such as sleep disturbances and vision problems. Lin et al ( 18 ) also found similar knowledge gaps about concussions. Both studies advocate for more specific education on concussion.…”
Section: Discussionmentioning
confidence: 69%
“…As for coaches, McLeod et al (10) and Lin et al (18) both reported that while coaches were knowledgeable, further education was necessary. McLeod et al (10) found that, while coaches could identify overt symptoms of concussion, they could not identify more subtle signs and symptoms such as sleep disturbances and vision problems.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a cross-sectional, population-based, survey study including both youth rugby athletes and their coaches of the Veneto region, the Italian region with the highest rate of youth rugby participation. For each of these 2 target populations, an online questionnaire was developed based on previous studies assessing concussion knowledge and behaviors among youth athletes 14,19,[21][22][23][24][25][26][27][28] and their coaches, 11,[15][16][17]29,30 involved in different types of sport. Questionnaires were developed in Italian by 2 authors (M.B.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, concussion management and compliance with return-to-play (RTP) guidelines remain suboptimal among both athletes and coaches, even within these countries. [11][12][13][14][15][16][17] Thus, in countries where such policies are missing or limited, it is likely that awareness of appropriate management and compliance with RTP guidelines are even less than suboptimal. This is particularly concerning for countries where contact sports are highly practiced, such as Italy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation